THE RELATIONSHIP BETWEEN MATERNAL CHARACTERISTICS AND INTRAOPERATIVE HYPOTENSION DURING CESAREAN SECTION USING SPINAL ANESTHESIA - Tri Budi Santoso; Widodo Widodo; Nurul Istiqomah; Heni Purwaningsih (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2024)
The incidence of hypotension as a complication of spinal anesthesia in mothers who gave birth by cesarean section can occur due to various factors such as height, age, weight. The incidence rate in Indonesia in 2017 was 983 cases. In the preliminary study, there were 352 deliveries, of which 108 were delivered by cesarean section using spinal anesthesia techniques. Objective: to determine the relationship between maternal characteristics and the incidence of intraoperative hypotension for sectio caesarea using spinal anesthesia at Hospital